Automated visual tracking of crack growth in coupon and component level fatigue testing using thermoelastic stress analysis. (October 2022) - Brooks, Chris; Rajic, Nik
Abstract: An automated system capable of visually detecting the two dimensional location of a crack in metal is presented. A peak-detection algorithm is applied to the thermoelastic signal component caused by heat diffusion, obtained from thermoelastic stress analysis using an industrial microbolometer, which is mounted on motion stages, allowing two dimensional tracking of the crack. The system is experimentally validated on coupons under constant amplitude loading, with the crack tip location estimates compared against measurements from an optical microscope. The system is also applied to monitoring crack growth on a geometrically complex section of an aircraft wing under representative flight-spectrum loading. Highlights: Automated crack growth monitoring using thermoelastic stress analysis. Thermoelastic stress analysis performed using low-cost industrial microbolometer. Monitors the crack growth path in two dimensions in near real-time. Movement stages allow for high spatial resolution on larger specimens. Application of crack growth monitoring to wing section with complex geometry.